Surgical management of avascular necrosis of femoral head in young adults treated with uncemented total hip replacement - Reddy, Vijaya Bhaskar; Chary, N. Brahma; Nikitha, Kacham (International Journal of Research in Orthopaedics, 2021)
Background: Normal hip joint is subjected to many stresses during daily activities performed by an individual. Since it is one of the major weight bearing joints of the body, its normal function is necessary for daily activities. Avascular necrosis (AVN) of the femoral head is one of the common causes of painful hip in a young adult. Core decompression, fibular sturt graft can be considered in early stages, total hip arthroplasty in later stages of AVN of femoral head. Methods: This is a retrospective study of 30 patients following uncemented total hip replacement, who were operated between August 2017 and March 2020 at MNR medical college and hospital, Sangareddy. They were followed up for a minimum period of 1 year and evaluated using Harris hip scoring system. Harris hip score is designed specifically for measuring functional outcomes in hip arthroplasty. Results: There was a significant improvement in function as measured with the Harris hip score. The overall preoperative Harris hip score was 43, which remarkably improved to 89 postoperatively. The results observed, showed that all patients had good to excellent results, (Harris hip score ≥0) thus showing a good degree of pain relief, improvement in function and range of motion. Conclusions: Although the use of total hip arthroplasty in young patients will more likely necessitate future revision surgery, the consistent relief of pain and good functional results have made this procedure an attractive treatment choice for the debilitating arthritis resulting from osteonecrosis of the femoral head.